Civil and Administrative Responsibility of PPAT for Sale and Purchase Deeds of Joint Property Made Without the Consent of the Spouse: Analysis of Decision Number 909 PK/PDT/2020 - David Efratha Lambe; Tjempaka Tjempaka (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The existence of joint property in a marriage has the legal consequence that any transfer of rights to it must obtain the consent of both spouses. However, in land practice, it is still found that Deeds of Sale and Purchase (AJB) are made by Land Deed Officials (PPAT) without ensuring such consent, thus creating legal uncertainty and opening up the potential for disputes. This situation emphasizes the importance of examining the role and responsibilities of PPATs as public officials who are obliged to guarantee the formal and material validity of every deed they make. Based on this context, this study examines the civil liability of PPATs for the creation of AJBs of joint property without the consent of the spouse by analyzing Decision Number 909 PK/Pdt/2020. This study uses a normative juridical method through a statutory regulatory approach and a case approach. The results of the study indicate that the sale and purchase of land that constitutes joint property without the consent of the spouse is invalid and can be canceled or nullified by law because it does not meet the subjective requirements of the agreement in Article 1320 of the Civil Code and is contrary to the provisions of marriage law. PPATs can be held civilly liable if their negligence in verifying marital status and the validity of documents causes harm to the parties. Decision Number 909 PK/Pdt/2020 confirms that a Deed of Sale and Purchase (AJB) made without the consent of a spouse can be revoked, resulting in legal consequences for the Land Deed Official (PPAT), the seller, and the buyer. However, buyers who have acted in good faith are still entitled to legal protection in accordance with Supreme Court jurisprudence. This study recommends that Land Deed Officials (PPAT) increase their vigilance by checking marital status, verifying documents, and requesting written consent from their spouse in every joint property transaction. The government needs to clarify technical guidelines, strengthen oversight, and provide competency training for Land Deed Officials (PPAT).